Pembrolizumab versus bevacizumab plus modified FOLFOX6 in metastatic MSI-H/dMMR colorectal cancer: a multicenter retrospective study with CT evaluation - Chen, Jiaqi; Yu, Weiguang; Xia, Xiaobo; Zhao, Yang; Tang, Qiang; Zhang, Yunxiang; Zhang, Yijie; Zhang, Haoyu; Zhang, Zhong; Zhang, Xiaoyan; Lou, Jianghua (Frontiers in Oncology, 2025)
ObjectiveThe optimal therapeutic strategy for metastatic microsatellite instability-high/mismatch repair-deficient (MSI-H/dMMR) colorectal cancer (CRC) remains uncertain. This multicenter retrospective study compared the efficacy and safety of pembrolizumab monotherapy versus bevacizumab combined with modified FOLFOX6 (mFOLFOX6) in this molecularly defined population.MethodsConsecutive patients with metastatic MSI-H/dMMR CRC treated with pembrolizumab or bevacizumab plus mFOLFOX6 at two tertiary centers (2017–2024) were analyzed. Dual primary endpoints included overall survival (OS) and progression-free survival (PFS); secondary endpoints encompassed incidence of grade ≥3 treatment-emergent adverse events (AEs).ResultsAmong 58 eligible patients (PE: n=30; BF: n=28), the PE cohort demonstrated a significantly higher objective response rate (ORR) compared to the BF cohort (XX% vs XX%, p=0.030) after a median follow-up of 18.0 months (IQR: 1.0–24.0). Survival analyses revealed superior outcomes in the PE cohort, with a median OS of 12.0 months (95% CI: 10.2–14.1) versus 8.8 months (95% CI: 7.1–9.6) in the BF cohort (HR=0.55, 95% CI: 0.29–0.56; p=0.02). Similarly, median PFS was prolonged in the PE cohort (7.0 months, 95% CI: 5.3–9.3) relative to the BF cohort (3.7 months, 95% CI: 2.2–5.4; HR=0.46, 95% CI: 0.24–0.89; p<0.001). No statistically significant intergroup differences were observed in grade ≥3 treatment-emergent AE rates.ConclusionPembrolizumab monotherapy significantly improved survival over bevacizumab-based chemotherapy in metastatic MSI-H/dMMR CRC, with a manageable safety profile. These results reinforce PD-1 inhibitors as first-line therapy for this population, while highlighting tumor mutation burden (TMB) and tumor burden as critical biomarkers for personalized strategies.